The Measurement of Sucrose Content of Sugar Cane Using Ultrasonic Waves - Amoranto Trisnobudi; Tjia Liong Hoei; Enung Rosihan Nugraha (Jurnal Teknologi dan Industri Pangan, 2001)
The measurement of sucrose content of sugar cane is usually carried out by using polarimeter and Brix Wager scale. These two apparatus are operated manually so that the accuracy of the measurement results is depended on the operator skill. To overcome this problem we have developed an alternative method that can measure the sucrose content more quickly and accurately than the conventional methods. This new method was carried out by using ultrasonic waves whose velocity depends on the sucrose content. Firstly, the electronic apparatus used was calibrated with 37 samples of sugar cane with various sucrose content from 4.46 % to 7.29 %. The result of this calibration was an empirical equation between the ultrasonic wave velocity V and the sucrose content R, i.e. R = 2.65 V2 - 11,95 V + 17,65 where R in % and V in km/s. Then this equation was stored as database in a computer program that will be used to calculate the sucrose content. Finally, this sucrose content measurement system was tested by using 30 samples of sugar cane. The maximum error of the measurement result was 6.4 %.